Factors Influencing The Extent of Accounting Information Usage In Cooperatives In The Province of Yogyakarta Special Region - Sungkono Sungkono (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2013)
Accounting information should be used by interested parties (stakeholders) as one of the basic for business decision making. In fact, accounting information has not been used optimally, especially by the principals of SMEs, including cooperatives. Many factors affect the extent of usage of accounting information, namely the scale of business, business age, type of business, manager education and training of accounting. This article presents the results of research on the factors that affect the extent of the usage of accounting information by the cooperative,it examines the influence of scale, age, business and accounting training on the extent of the usage of accounting information by the cooperative. This research took 30 cooperatives in the district of Sleman as the sample. The sampling method used was 'purposive random sampling'. The hypothesiswhich was tested with multiple regression test shows that the three factors, namely business scale, age of business and accounting training both totally and partially affect the extent of the usage of accounting information by the cooperative